Analysis of interleukin-20 receptor complexes in trabecular meshwork cells and effects of cytokine signaling in anterior segment perfusion culture - Kate E.; Yong-feng; Ying Ying; Mark R.; Mary K. (Molecular Vision, 2019)
Purpose: Inflammatory responses may be involved in the glaucomatous process. Our previous studies mapped a T104M mutation in interleukin-20 receptor beta (IL-20RB) in a family with primary open angle glaucoma (POAG). IL-20RB can heterodimerize with IL-20RA to propagate signals from IL-20 family cytokines, IL-19, IL-20, and IL-24 (the type I receptor complex), or it can heterodimerize with IL-22RA to propagate signals from IL-20 and IL-24 (type II receptor complex). In this study, we investigated IL-20 heterodimeric receptor complexes in the trabecular meshwork (TM) compared to dermal fibroblast cell cultures, and examined the phosphorylation of signal transducer and activator of transcription (STAT)-1, -3, and -5 following exposure to IL-20 family cytokines. Additionally, we determined the effects of IL-20 family cytokines on outflow rates in anterior segment perfusion culture, an in vitro model of intraocular pressure (IOP) regulation.